SATU SURO NIGHT TRADITION ON IKATAN KELUARGA JAWA RIAU (IKJR) AT SUKA MULYA SP II OF KAMPAR REGENCY - Julianti, Tri; ", Syafrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Satu suro night tradition is a tradition which is held on the turnover eve of Islamic new year 1 Muharram which is better known as Suroan for Javanese community. Each region has difference way to perform this tradition. It has been done since long ago by an association of Javanese family located in Kampar regency with the name is Ikatan Keluarga Jawa Riau (IKJR). The purpose of this research was to analyze the process or the implementation of Satu suro night tradition by IKJR, and to analyze the meaning, value contained, and the impact of it. In this research, the researcher used qualitative research type or often called as naturalistic research methods because the research was done on natural conditions. The subjects of this research were determined by Purposive Sampling way that consists of Chairman, Secretary, Treasurer, and Vice Chairman of DPD-IKJR Kampar regency, and also the Head of Suka Mulya SP II Village. The researcher used observation, in-depth interviews, and documentation to collect the data. In this research, the researcher had analyzed how this Satu suro night tradition was done by IKJR region Kampar. Based on the interviews and observations that had been done, the researcher found that IKJR conducted the tradition by holding various social activities before the evening peak of Satu suro night tradition held, and on the evening peak was also held various activities ranging from dance offerings, Kampar bersholawat, to all-night shadow puppet performances. The meaning that could be taken from this tradition was to thrill the Javanese culture (menguri-uri budoyo Jowo). The most important was as an expression of gratitude for the favors that had been given by Allah Subhana Wa Ta'ala and gratitude for a better life after doing transmigration from Java to Riau. This tradition also had a very positive impact for the people who attended it and also for the merchants who peddled their wares.Keywords: Tradition, Satu Suro, Javanese